General informatics teaching with B-Learning teaching model - Dung, Nguyen The; Fatmawati, Diani (Jurnal Pendidikan Biologi Indonesia, 2018)
Blended learning (B-learning), a combination of face-to-face teaching and E-learning-supported-teaching in an online course, and Information and Communication Technology (ICT) tools have been studied in recent years. In addition, the use of this teaching model is effective in teaching and learning conditions in which some certain subjects are appropriate for the specific teaching context. As it has been a matter of concern of the universities in Vietnam today, deep studies related to this topic is crucial to be conducted. In this article, the process of developing online courses and organizing teaching for the General Informatics subject for first-year students at the Hue University of Education with B-learning teaching model will be presented. The combination of 60% face-to-face and 40% online learning.